2023
DOI: 10.3390/ijms24065435
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Expression of the Circadian Clock Gene Cryptochrome 1 Causes Abnormal Glucometabolic and Cell Growth in Bombyx mori Cells

Abstract: Cryptochrome is the earliest discovered photoreceptor protein in organisms. However, the effect of CRY (BmCRY), the clock protein in Bombyx mori, on the body or cell metabolism remains unclear. In this study, we continuously interfered with the expression of the BmCry1 gene (Cry1-KD) in the silkworm ovary cell line (BmN), and the BmN cells developed abnormally, with accelerated cell growth and a smaller nucleus. Metabolomics was used to identify the cause of the abnormal development of Cry1-KD cells based on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Furthermore, Homma et al, (2022), having knocked out not only per , tim , Clk and cyc but also cry1 and cry2 , reported effects on temperature-dependent diapause induction, finding disruption in cry2 but not cry1 knockout. In recent years, studies using the cry1 knockout strain have revealed cry1 ’s role in hatching rhythm, immunity, cell growth, and hormonal control of development (Qiu et al, 2022, 2023a, 2023b; Yuan et al, 2023). However, the involvement of cry genes in B. mori photoperiodism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Homma et al, (2022), having knocked out not only per , tim , Clk and cyc but also cry1 and cry2 , reported effects on temperature-dependent diapause induction, finding disruption in cry2 but not cry1 knockout. In recent years, studies using the cry1 knockout strain have revealed cry1 ’s role in hatching rhythm, immunity, cell growth, and hormonal control of development (Qiu et al, 2022, 2023a, 2023b; Yuan et al, 2023). However, the involvement of cry genes in B. mori photoperiodism remains unclear.…”
Section: Introductionmentioning
confidence: 99%